Challenges of Implementing Electronic Procurement (E-Procurement) in the North Gorontalo District Government - Pakaya, Pahlawanti; Sulila, Ismet; Agusalim, Alfiah; Tantu, Romi (Program Studi Ilmu Pemerintahan, 2025)
This research examines the implementation of contracts for the electronic procurement of goods and services in Gorontalo Regency, especially through the LPSE application. Even though the e-Procurement process has been running according to the rules, there are obstacles both in implementation and operational policies. Implementation of this policy involves five key stages, of which procurement planning and preparation are the most crucial aspects. The main problem faced is a lack of understanding and mastery of human resources, as well as weak coordination. Such factors, through qualitative methods, found that several factors that influence the success of policies such as: resource factors, disposition and bureaucratic structure also influence the effectiveness of implementation. Decreased communication between users and providers, as well as the low percentage of officials who have procurement certification, is a challenge in itself. In addition, employee resistance to electronic systems and the need for increased internal coordination between officials were also identified. However, even though e-Procurement has been implemented, improvements are still needed in aspects of human resources and bureaucratic structure to increase the effectiveness of goods and services procurement policies within the Gorontalo Regency Regional Government. Penelitian ini mengkaji pelaksanaan kontrak pengadaan barang dan jasa secara elektronik di Kabupaten Gorontalo, khususnya melalui aplikasi LPSE. Meskipun proses e-Procurement telah dijalankan sesuai dengan aturan, terdapat kendala baik dalam pelaksanaan maupun operasional kebijakan. Implementasi kebijakan ini melibatkan lima tahapan kunci, di mana perencanaan dan persiapan pengadaan menjadi aspek yang paling krusial. Masalah utama yang dihadapi adalah kurangnya pemahaman dan penguasaan sumber daya manusia (SDM), serta koordinasi yang lemah. Melalui metode kualitatif, ditemukan bahwa beberapa faktor yang mempengaruhi keberhasilan kebijakan antara lain: faktor sumber daya, disposisi, dan struktur birokrasi turut mempengaruhi efektivitas implementasi. Komunikasi yang menurun antara pengguna dan penyedia, serta rendahnya persentase pejabat yang memiliki sertifikasi pengadaan, menjadi tantangan tersendiri. Selain itu, resistensi pegawai terhadap sistem elektronik dan perlunya peningkatan koordinasi internal antarpejabat juga diidentifikasi. Dengan demikian, meskipun e-Procurement telah dilaksanakan, masih dibutuhkan perbaikan dalam aspek sumber daya manusia dan struktur birokrasi untuk meningkatkan efektivitas kebijakan pengadaan barang dan jasa di lingkungan Pemerintah Daerah Kabupaten Gorontalo.